2015
DOI: 10.1039/c5cp02481a
|View full text |Cite
|
Sign up to set email alerts
|

Predicting near-UV electronic circular dichroism in nucleosomal DNA by means of DFT response theory

Abstract: It is demonstrated that time-dependent density functional theory (DFT) calculations can accurately predict changes in near-UV electronic circular dichroism (ECD) spectra of DNA as the structure is altered from the linear (free) B-DNA form to the supercoiled N-DNA form found in nucleosome core particles. At the DFT/B3LYP level of theory, the ECD signal response is reduced by a factor of 6.7 in going from the B-DNA to the N-DNA form, and it is illustrated how more than 90% of the individual base-pair dimers cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…The necessity of including a large number of chromophores makes at the moment unfeasible the application of Wave-Function based ab initio calculations. On the other hand, the results we report show that, when adopting a suitable functional, TD-DFT calculations, confirming the good performances obtained on DNA single and double strands, [70][71][72][73][74][75] well reproduce the effect of stacking geometry on the absorption and ECD spectra of G4s (Figure 2-4). 27,42 It is nowadays well assessed that the excited states in absorption are delocalized over multiple bases and that the coupling between the different chromophores is determined by the G4 conformation, giving account for the different ECD spectra.…”
Section: Discussionsupporting
confidence: 80%
“…The necessity of including a large number of chromophores makes at the moment unfeasible the application of Wave-Function based ab initio calculations. On the other hand, the results we report show that, when adopting a suitable functional, TD-DFT calculations, confirming the good performances obtained on DNA single and double strands, [70][71][72][73][74][75] well reproduce the effect of stacking geometry on the absorption and ECD spectra of G4s (Figure 2-4). 27,42 It is nowadays well assessed that the excited states in absorption are delocalized over multiple bases and that the coupling between the different chromophores is determined by the G4 conformation, giving account for the different ECD spectra.…”
Section: Discussionsupporting
confidence: 80%
“…It has been demonstrated that ECD in linear and nucleosomal forms of DNA can be simulated by means of summing spectra from base‐pair dimers and thereby effectively transform the spectrum calculation of a large‐scale system into a large number of calculations for moderately sized systems . Similarly, ECD spectra of very short peptides and unfolded oligo‐peptides/proteins are in close agreement but, at the same time, the involvement of dynamic explicit water molecules in the electronic structures of accessible states makes the situation more complex and renders classical excitonic models unsuitable .…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Their results show a very good agreement with the experimental CD fingerprint of the adenine-thymine base pairs homo-polymers in the near-ultraviolet region, corresponding to two positive bands at 260 and 283 nm and a more intense negative band at 249 nm. Furthermore, Norman et al ( 2015 ) tackled the case of the 147 base pairs long nucleosomal DNA (pdb code: 1KX5) employing a similar procedure. The results demonstrated the influence of the super-helical configuration on the CD spectra, including a hypsochromic shift of the band at 269 nm and a strong decrease of its intensity.…”
Section: Circular Dichroism Modelingmentioning
confidence: 99%